Underwater noise characterization of down-the-hole pile driving activities off Biorka Island, Alaska. (November 2020) - Guan, Shane; Miner, Robert
Abstract: Although down-the-hole (DTH) pile driving is increasingly used for in-water pile installation, the characteristics of underwater noise from DTH pile driving is largely undocumented and unstudied. This study presents a comprehensive analysis of the noise characteristics during DTH pile driving of two steel pipe piles in shallow waters off southeast Alaska. The results showed that single-strike sound exposure levels measured at 10 m were 147 and 145 dB re 1 μPa 2 s with a total of 21, 742 and 38, 631 hammer strikes, with cumulative sound exposure levels to install each pile at 192 and 191 dB re 1 μPa 2 s, respectively. Though noise levels from a single strike was lower than impact pile driving of a similar pile, the cumulative sound exposure levels are likely comparable due to the much higher striking rate. Highlights: In-water down-the-hole pile (DTH) driving produces intense underwater noise. Measurements describe DTH pile driving noise characteristics off Biorka Island, Alaska. Single-strike sound exposure levels measured at 145–147 dB re 1 μPa 2 s at 10 m. Underwater noise from DTH pile driving could impact aquatic animals.